Determine the Diagnostic Accuracy of High Beta HCG Levels in Predicting Pregnancy Induced Hypertension - Zille Huma, Shagufta Jabbar, Fariha Arshad, Sadaf Kashif, Rafia Ali, Naila Khawer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the diagnostic accuracy of high beta HCG levels (>2 median concentration measured) in predicting pregnancy induced hypertension. Study design: Cross-sectional analytical study. Place and duration of study: Department of Obstetrics & Gynaecology, Social Security Hospital, Lahore from 1st January 2021 to 31st December 2021. Methodology: One hundred and fifty pregnant females at 13-20 weeks of gestation were included. A 3cc blood sample was withdrawn from each women and serum was separated. The serum was stored at -20°C until analysis of β HCG test. This test was analyzed via enzyme-linked immunosorbent assay. The sensitivity of the test was 86.5% and specificity was 96.8%. Each woman was followed till delivery and her status of hypertension which was induced due to pregnancy was observed. Results: The mean age was 31.5±6.2 years. The value of 2 median concentration measured showed that 23 cases had a value less or equal to 2 while 60 cases were those having a value greater than 2. The diagnostic accuracy of this test was 92.6%. There were 69.8% cases of PIH having beta HCG levels greater than 71000 mIU/ml and six cases with level of beta HCG higher than 100000 mIU/ml. Conclusion: Pregnancy induced hypertension is significantly associated with higher level of beta HCG and has an efficient diagnostic accuracy.